Influence of forming pressure on frost resistance of ceramics - Subota, Іrіna; Spasonova, Larysa; Sholom, Аnastasia (Technology audit and production reserves, 2021)
The object of research is low-melting clays of the Kyiv region (Ukraine). The work is devoted to the study of obtaining ceramic materials resistant to low temperatures. Frost resistance is one of the most important characteristics for regions in which ceramic materials are used with frequent temperature transitions through 0 °C. The production of frost-resistant ceramic wall materials is determined by the type of raw materials and technological production parameters. The main technological methods for increasing frost resistance are: the use of less dispersed clays; batch homogenization; formation of raw material without textural defects and prevention of cracks during drying and firing. The work shows that the existing methods for increasing frost resistance can be implemented by reducing water absorption due to the creation of a microporous structure with predominantly closed pores by increased pressure of a semi-dry method of formation. An increase in the pressing pressure leads to an increase in the number of contacts of the molecules of the ceramic mass at the stage of formation. Due to this, the strength of the molded samples at a pressing pressure of more than 30 MPa is higher compared to samples molded by the plastic method. It was also found that an increase in the pressing pressure makes it possible to speed up the drying process of ceramic products, reducing energy consumption for their production. Due to an increase in the pressing pressure to 50 MPa, the strength of samples obtained by semi-dry pressing is 55.4 MPa, while for samples during plastic formation it is 22.9 MPa. Water absorption, on the contrary, for dry pressing is 9.3 %, while for plastic pressing it is 12.2 % at a firing temperature of 1000 °C. It is shown that increasing the pressing pressure is an effective way to improve the quality of ceramic materials based on local low-plasticity clay raw materials. Saving natural and energy resources, developing new sources of raw materials and comprehensive improvement of products with environmental friendliness of production remain important today.